Strategic Management In Improving The Effectiveness of Private Islamic Religious College In Kepulauan Riau - Subekti, Imam; Syukri, Ahmad; Anwar, Kasful (TANJAK, 2024)
The aim of this research is to find out the level of effectiveness of higher education institutions in implementing strategicmanagement seen from strategy formulation, strategy implementation and strategy evaluation in increasing the effectiveness of higher education institutions in the Kepulauan Riau. The theories used are strategic management theory and effectiveness theory. This research uses qualitative methods in the form of field research. This research took the location of a private Islamic religious college in the Kepulauan Riau. The research subjects were foundation administrators, university leadership, lecturers and educational staff. The types of data in this research are divided into two, namely primary data andsecondary data. In collecting data, the methods used were observation, interviews and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions and verification. The results of thisresearch found that the implementation ofstrategies at private Islamic religious universities in the Kepulauan Riau was considered poor in terms of increasing the effectiveness of higher education. Based on strategic management and effectiveness theory, various indicators can be used; 1) strategy formulation, 2) strategy implementation, 3) strategy evaluation. Apart from the need for strategic management (formulation, implementation, evaluation), based on effectiveness theory, increasing the effectiveness of private Islamic religious universities in the Kepulauan Riaucan be done by: a) improving quality, b) promotion, c) increasing cooperation, d) implementing guarantees quality, e) student services, and f) increasing research and scientific publications by lecturers. This will have an impact on increasing the effectivenessof tertiary institutions, which will ultimately increase public interest in continuing their studies at private Islamic religious tertiary institutions in the Kepulauan Riau Province.